Penguatan Festival Enam Suku Barikan Kubro melalui Penghadiran Karya Tari Baru Renjana Karimunjawa - Putro, Renaldi Lestianto Utomo; Dewi, Maharani Luthvinda; Supendi, Eko; Kuncoro, Jonet Sri (Institut Seni Indonesia Surakarta, 2023)
Community service activities in Karimunjawa Village aim to strengthen the Barikan Kubro Six Tribe Festival. The goal is motivated by the community's willingness to welcome the post-pandemic period by reactivating festival activities that had stopped. Festival activation has unresolved homework from the last event hosting: no new art creations image the culture of the people of Karimunjawa. New art creations, especially dance in Karimunjawa, are not growing due to a lack of experts and knowledge about dance creation. Therefore, the problem that must be solved is how to create new dance works that can be used to strengthen the festival's implementation. The solution is to create dance works with the local community's cultural background, train the results of the works composition to the public, and promote the composed works through performances. The approach is based on Skinner's concept of habituating behavior modification as a form of cultural reinforcement. Implementation of the creation includes; 1) the preparation stage and 2) the implementation stage. The result achieved from this program is the creation of the dance